THE EFFECT OF STUDENT ENGAGEMENT TO UNDERSTANDING OF ACCOUNTING CONCEPTS - Effi Aswita Lubis; Azizul Kholis; La Hanu; Agus Rahmadsyah; Widyawati Syafitri (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
The purpose of this study is to find out how important the role of student involvement in understanding accounting concepts is. This research was conducted at SMK Negeri 1 Medan The population in this study were all students of class X Accounting at SMK Negeri 1 Medan City for the 2020/2021 academic year which consisted of 144 students and consisted of 4 classes, while the sampling technique used in this study was probability sampling with a sample of 59 students. For the actual data and description of the topic to be studied, the researcher used several data collection methods, namely; interview and Questionnaire/Questionnaire. Data analysis techniques in this study are descriptive statistical analysis, product moment correlation analysis, simple regression analysis. The results of the analysis and discussion conducted regarding the effect of student involvement on the understanding of accounting concepts for students in SMK N 1 Medan City, it can be concluded as follows: There is a positive and significant effect of student involvement (X) on understanding accounting concepts (Y) for class X SMK students N1 Medan and Based on the coefficient of determination, student involvement has an influence on students' understanding of accounting concepts by 49.5%. While 50.5% is explained by other factors or variables that are not included in this regression analysis and are not studied in this study.